Students’ Perception on Peer Revisions of Deemphasizing Grammar Correction in SMA Mulia Bhakti, Makassar, South Sulawesi - Jelita Purnamasari; Baso Jabu; Abdul Halim (Universitas Negeri Makassar, 2016)
This research are aims at (i) investigating perceptions of learners about the implementation of peer revision of deemphasizing grammatical correction at SMA Mulia Bhakti Makassar, (ii) finding out the factors which influenced the implementation of peer revision of deemphasizing grammar correction at SMA Mulia Bhakti Makassar, and (iii) finding out how the peer revision of deemphasizing grammar correction is implemented at SMA Mulia Bhakti Makassar. The researcher conducted qualitative method. The data resources were 11th-grade students at SMA Mulia Bhakti Makassar who had experience in the practice of peer revision of deemphasizing grammar correction. The result showed that, (i) the researcher found the students’ positive perception and negative perception on peer revision of deemphasizing grammatical correction. The positive perceptions were students became more active, developed their critical thinking, leaded them to students’ self-directed learning, and decreased students’ writing apprehension while the negative perceptions were it created overly critical comments and also conflict (ii) the factors influenced the implementation were students’ ability as reviewer and sitting them in collaborative work (iii) the steps of peer revision of deemphasizing grammatical correction at SMA Mulia Bhakti Makassar consisted of six steps, namely writing, revision, first rewriting, editing, second rewriting, and scoring.